Processing Prescriptively Incorrect Comparative Particles: Evidence From Sentence-Matching and Eye-Tracking - Hubers, Ferdy; Redl, Theresa; de Vos, Hugo; Reinarz, Lukas; de Hoop, Helen (Frontiers in Psychology, 2020)
Speakers of a language sometimes use particular constructions which violate prescriptive grammar rules. Despite their prescriptive ungrammaticality, they can occur rather frequently. One such example is the comparative construction in Dutch and similarly in German, where the equative particle is used in comparative constructions instead of the prescriptively correct comparative particle (Dutch beter als Jan and German besser wie Jan “lit. better as John”). In a series of three experiments using sentence-matching and eye-tracking methodology, we investigated whether this grammatical norm violation is processed as grammatical, as ungrammatical, or whether it falls in between these two. We hypothesized that the latter would be the case. We analyzed our data using linear mixed effects models in order to capture possible individual differences. The results of the sentence-matching experiments, which were conducted in both Dutch and German, showed that the grammatical norm violation patterns with ungrammatical sentences in both languages. Our hypothesis was therefore not borne out. However, using the more sensitive eye-tracking method on Dutch speakers only, we found that the ungrammatical alternative leads to higher reading times than the grammatical norm violation. We also found significant individual variation regarding this very effect. We furthermore replicated the processing difference between the grammatical norm violation and the prescriptively correct variant. In summary, we conclude that while the results of the more sensitive eye-tracking experiment suggest that the grammatical norm violation is not processed completely on a par with ungrammatical sentences, the results of all three experiments clearly show that the grammatical norm violation cannot be considered grammatical, either.